Association of early administration of furosemide with improved oxygenation in patients with acute heart failure. (15th June 2021) - Mikami, Takafumi; Ishii, Masanobu; Yamamoto, Nobuyasu; Marume, Kyohei; Nakai, Michikazu; Ogata, Soshiro; Kaichi, Ryota; Ikebe, Sou; Mori, Takayuki; Komaki, Soichi; Kusaka, Hiroaki; Toida, Reiko; et al.
Abstract: Aims: Optimal pharmacological treatment for chronic heart failure has been established. However, treatments that can improve the prognosis of acute heart failure (AHF) are controversial. Although intravenous diuretics may be one optimal treatment option, little evidence has shown the effect of early administration of diuretics on clinical outcomes in patients with AHF. The aim of this study was to evaluate the association between door‐to‐furosemide (D2F) time, improved oxygenation, and in‐hospital mortality in patients hospitalized for AHF. Methods and results: We screened 494 patients hospitalized for AHF in Miyazaki Prefectural Nobeoka Hospital. AHF patients who were treated with intravenous furosemide within 24 h of arrival at the hospital were included in this study. D2F time was defined as the time from patient arrival at the hospital to the first intravenous dose of furosemide. The early administration group was defined as those with D2F time ≤60 min, whereas the non‐early group was defined as those with D2F time >60 min. The primary outcome was the rate of improved oxygenation at Day 1. The secondary outcomes were in‐hospital mortality and cardiac death. There were 219 patients treated with the first intravenous dose of furosemide within 24 h analysed after the exclusion of 275 patients. The median D2F time was 55 min (interquartile range: 30–120 min) in the final cohort. The early administration group included 121 patients (55.3%). The rate of improved oxygenation was higher in the early group than the non‐early group [median 16.7% (interquartile range: 0.0–40.0) vs. 0.0% (0.0–20.6), respectively, P  < 0.001]. During the study period, there were six patients (5.0%) with in‐hospital mortality in the early group and nine patients (9.2%) in the non‐early group ( P  = 0.218). Cardiac death was observed less frequently in the early group than in the non‐early group, but without statistical significance (3.3% and 9.2%, respectively) ( P  = 0.067). The univariable logistic regression analyses showed that early administration of furosemide was associated with improved oxygenation [odds ratio (OR): 2.26; 95% confidence interval (CI): 1.31–3.91; P  = 0.004], but not with in‐hospital mortality (OR: 0.52; 95% CI: 0.18–1.50; P  = 0.225) or cardiac death (OR: 0.34; 95% CI: 0.10–1.13; P  = 0.079). In multivariable analyses adjusted for risk score or relevant variables, early administration of furosemide was consistently associated with improvement of oxygenation. Conclusions: The present study showed that in AHF patients, the early administration of furosemide was associated with improved oxygenation.